GASTROINTESTINAL ACID-RELATED DISEASES AND ISCHEMIC HEART DISEASE: PATHOPHYSIOLOGICAL LINKS AND CLINICAL IMPLICATIONS - Raupov Abdurahmon Ortiq o’g’li (KONFERENSIYALAR, 2025)
Аnnotation.  This  review  summarizes  key  evidence  on  the  interrelations between  gastroesophageal  reflux  disease,  peptic  ulcer  disease,  liver  disorders, inflammatory  bowel  diseases,  and  ischemic  heart  disease.  It  highlights  both common  and  specific  risk  factors,  as  well  as  mechanisms  of  comorbidity, including those linked to standard treatments. Based on meta-analyses and large-scale population studies, the review aims to support the improvement of current clinical guidelines for managing comorbid conditions.